Vascular endothelial profilin-1 drives a protumorigenic tumor microenvironment and tumor progression in renal cancer - Gau, David; Daoud, Andrew; Allen, Abigail; Joy, Marion; Sagan, April; Lee, Sanghoon; Lucas, Peter C.; Duensing, Stefan; Boone, David; Osmanbeyoglu, Hatice U.; Roy, Partha (The journal of biological chemistry, 2023)
Overexpression of actin-binding protein profilin-1 (Pfn1) correlates with advanced disease features and adverse clinical outcome of patients with clear cell renal carcinoma, the most prevalent form of renal cancer. We previously reported that Pfn1 is predominantly overexpressed in tumor-associated vascular endothelial cells in human clear cell renal carcinoma. In this study, we combined in vivo strategies involving endothelial cell-specific depletion and overexpression of Pfn1 to demonstrate a role of vascular endothelial Pfn1 in promoting tumorigenicity and enabling progressive growth and metastasis of renal carcinoma cells in a syngeneic orthotopic mouse model of kidney cancer. We established an important role of endothelial Pfn1 in tumor angiogenesis and further identified endothelial Pfn1-dependent regulation of several pro- (VEGF, SERPINE1, CCL2) and anti-angiogenic factors (platelet factor 4) in vivo. Endothelial Pfn1 overexpression increases tumor infiltration by macrophages and concomitantly diminishes tumor infiltration by T cells including CD8+ T cells in vivo, correlating with the pattern of endothelial Pfn1-dependent changes in tumor abundance of several prominent immunomodulatory cytokines. These data were also corroborated by multiplexed quantitative immunohistochemistry and immune deconvolution analyses of RNA-seq data of clinical samples. Guided by Upstream Regulator Analysis of tumor transcriptome data, we further established endothelial Pfn1-induced Hif1α elevation and suppression of STAT1 activation. In conclusion, this study demonstrates for the first time a direct causal relationship between vascular endothelial Pfn1 dysregulation, immunosuppressive tumor microenvironment, and disease progression with mechanistic insights in kidney cancer. Our study also provides a conceptual basis for targeting Pfn1 for therapeutic benefit in kidney cancer.
Gesehen am 22.04.2024